Algorithms for Artificial Intelligence. - Rowe, Neil C.; Drusinsky, Doron (Computer (00189162), 2022)
Artificial intelligence and machine learning use a wide variety of algorithms. More than 60 years of research have shown that intelligent behavior requires a variety of methods. We discuss the major classes of algorithms and their uses.